Warm springs reduce parasitism of the cereal leaf beetle through phenological mismatch. (20th December 2012) - Evans, E. W.; Carlile, N. R.; Innes, M. B.; Pitigala, N.
Abstract Variation in weather among years may affect biological control of insect pests by influencing how well matched in phenology specialist parasitoids are with their pest hosts. A 10‐year study in western North America (Utah) revealed greater change with warm versus cool springs in the life cycle timing of the cereal leaf beetle (CLB), Oulema melanopus (L.), than of its principal enemy, the parasitoid wasp Tetrastichus julis (Walker). The beetle laid eggs, and larval populations developed in crop fields earlier on a calendar‐day basis, but nonetheless after more degree‐days had accumulated, in warmer than in cooler springs. The phenology of parasitism by wasps, in contrast, varied little among springs in relation to accumulated degree‐days. Consequently, in warmer springs, larval phenology of the CLB was delayed relative to adult parasitoid activity, and parasitism was reduced. Presently, a significant degree of biological control of the CLB results from parasitism by T. julis. By promoting phenological mismatch between host and parasitoid, however, a warming climate could weaken this biological control of the insect pest.